The efficacy and safety of vincristine, irinotecan and anlotinib in Epithelioid Sarcoma - Lu Xie; Xin Sun; Jie Xu; Xin Liang; Kuisheng Liu; Kunkun Sun; Rongli Yang; Xiaodong Tang; Wei Guo (BMC Cancer, 2024)
Abstract Background Epithelioid sarcoma is a rare soft tissue sarcoma characterized by SMARCB1/INI1 deficiency. Much attention has been paid to the selective EZH2 inhibitor tazemetostat, where other systemic treatments are generally ignored. To explore alternative treatment options, we studied the effects of irinotecan-based chemotherapy in a series of epithelioid sarcoma patients. Methods We retrospectively reviewed data from patients with metastatic or unresectable epithelioid sarcoma at the Peking University People’s Hospital treated with irinotecan (50 mg/m2/d d1-5 Q3W) in combination with Anlotinib (12 mg Qd, 2 weeks on and 1 week off) from July 2015 to November 2021. Results A total of 54 courses were administered. With a median follow up of 21.2 months (95% CI, 12.2, 68.1), the 5-year overall survival rate was 83.3%. Five of eight (62.5%) patients presented with unresectable localized lesions, including local tumor thrombosis and lymphatic metastasis. The other patients had unresectable pulmonary metastases. Six of eight (75%) patients had progressed following two lines of systemic therapy. The objective response rate reached 37.5% (three of eight patients) while stabilized disease was observed in 62.5% (five of eight) of patients. No patient had progressed at initial evaluation. At the last follow up, two patients were still using the combination and three patients had ceased the therapy due to toxicities such as diarrhea, nausea, and emesis. One patient changed to tazemetostat for maintenance and one patient stopped treatment due to coronavirus disease 2019 (COVID-19). Another patient stopped therapy as residual lesions had been radiated. Conclusions The combination of irinotecan and Anlotinib as a salvage regimen may be considered another effective treatment option for refractory epithelioid sarcoma. Trial registration This study was approved in the Medical Ethics Committee of Peking University People’s Hospital on October 28, 2022 (No.: 2022PHD015-002). The study was registered in Clinicaltrials.gov with identifier no. NCT05656222.